Changes in Serum Physiological and Biochemical Parameters of Male Swiss Albino Mice After Oral Administration of Metal Oxide Nanoparticles (ZnO, CuO, and ZnO plus CuO) - KARĞIN, DİCLE (SPRINGERNATURE, 2021)
Zinc oxide (ZnO) and copper oxide (CuO) nanoparticles (NPs) are widely used in medicine and industrial fields. They have negative effects such as hematoxic, cytotoxic, and genotoxic on animals. This research aimed to investigate the blood physiological and biochemical responses induced by ZnO-NP and CuO-NP individually or in combination in male Swiss albino mice. For purpose, NPs were given to mice with 100 mu l of water by oral gavage for 14 days. Three sublethal NP dose groups (1, 5, 25 mg/kg/day) and one control group (only received 100 mu l of water) were used in the experiments and serum metabolite (glucose, total protein, total cholesterol, triglyceride, cortisol, blood urea nitrogen, immunoglobulin G, and M), ions (Na, K, Cl, Mg, and Ca), and enzyme (ALT, AST, ALP, and LDH) levels were measured. ZnO-, CuO-, and ZnO+CuO-NPs especially higher doses (5 and 25 mg/kg/day) decreased all serum metabolite (except blood urea nitrogen), ions, and ALP while these nanoparticles increased ALT, AST, LDH, and blood urea nitrogen. These increases/decreases in all serum parameters were generally higher in mice treated with the ZnO+CuO-NP mixture compared to the ZnO-NP and CuO-NP groups alone. The study shows that serum biochemistry profiles can be used as indicators to assess nanoparticle toxicity on lipid, protein, and energy metabolisms, immune and enzyme systems, ion regulation, and tissue functions.
Keywords: Zinc; Copper; Nanoparticles; Mice; Blood parameters; SILVER NANOPARTICLES; TOXICITY; EXPOSURE; ENZYMES